DEVELOPING AL-QURAN INSTRUCTION MODEL THROUGH 3A (AJARI AKU AL-QURAN OR PLEASE TEACH ME AL-QURAN) TO IMPROVE STUDENTS’ ABILITY IN READING AL-QURAN AT BANDUNG ISLAMIC UNIVERSITY - Alhamuddin, Alhamuddin; Hamdani, Fahmi Fatwa Rosyadi Satria; Tandika, Dikdik; Adwiyah, Rabiatul (UPI Press, 2018)
This research has the intention to develop the model of Quran learning which is creative and innovative to increase students’ ability in reading the Quran. This method is applied by the use of puzzle game, iqro bar, and monopoly game, so that the students can recognize the Quran letters well and correctly. This research applied the research and development approach. The trial was done to all students in every faculty at UNISBA. The number of the students who participated in this research was 519. The sample was selected on the basis of students’ abilities in reading the Quran, especially the students who were in group E. The result of the research shows that the application of 3A learning media for the group that does not know Quran letters well significantly helped them recognize the Hijaiyyah letters easily. The process of learning was designed actively, creatively, effectively, innovatively, fun, and with student-centered approach. Based on the result, the researchers recommended do the further study as part of the design’s development and improvement of learning Quran through 3A media.